Revisiting the Trail of the Dios Buhawi Movement: Its Impact on the Revolutionary Struggle in the Southern Negros Oriental (1888-1898) - Cleope, Earl Jude Paul L. (Silliman Journal, 2022)
This paper deviates from the traditional and common practice of Cognitive History towards the call of modern historians to view history from the perspective of New Historicism. From this vantage point, this paper briefly presents the rebellion in southern Negros Oriental spearheaded by Dios Buhawi. Specifically, this paper will examine the poplarly-held notions that the so-called insignificant rebellions were led by remontados, bandidos, and tulisanes and thus were plain banditry. Hence their activities were considered unimportant to the revolutionary struggle. This paper maintains that the movement spearheaded by Buhawi a decade prior to the liberation of Negros initiated, influenced, and contributed significantly to the dynamic processes that culminated in the liberation of the island from Spain. Its greatest impact was manifested in the subsequent revolutionary activities of Leon Kilat in Cebu, Felipe Tayko in southern Negros Oriental, and Papa Isio in Negros Occidental, not to mention the numerous other personages who continued his cause but did not live to see the liberation.